Implementasi Algoritma Vizing Untuk Proses Pewarnaan Sisi Graf Pada Penjadwalan Kuliah - Sinaga, Tuty Handa; Sunandar, Hery; Murdani, Murdani; Aripin, Soeb (JURNAL RISET KOMPUTER (JURIKOM), 2020)
Dots coloring is coloring all points in graph ðº, so that each pair of directly connected points has a different color. Point coloring can be used to help solve the problem of preparing class schedules. One algorithm for solving graph coloring problems in college scheduling is the vizing algorithm. The results of graph coloring using the taboo search algorithm are used to arrange class schedules, so that there are no conflicting schedules meaning that no two courses taken by a student are carried out at the same time. Thus, time and space can be determined to carry out lectures so that a class schedule can be made. To make it easier to solve these problems, a program with vb2008 was created. The data entered in the form of courses, lecturers and student classes will be represented as point graphs. The coloring process starts from ð‘˜ = 1 so that the minimum color is obtained. The output produced by the program is in the form of class schedules that have been determined by time and space